Child education in islam: A study of abdullah nashih ‘ulwan’s thoughts in tarbiyatul aulad fil islam from the perspective of axiology and the rahmatan lil ‘alamin curriculum - Dian Permana; Usman Abu Bakar; Ahmad Mufrod Teguh Mulyo (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2025)
This study examines the thought of Abdullah Nashih ‘Ulwan in Tarbiyatul Aulad fil Islam through the lens of axiology and the Rahmatan lil ‘Alamin curriculum to understand the relevance of Islamic child education values in contemporary contexts. Arising from the need to integrate moral, spiritual, and humanistic values into curriculum development, this research aims to identify the foundational principles of child education according to ‘Ulwan and evaluate their contribution to constructing an Islamic curriculum oriented toward the common good. Using a qualitative library research approach and content analysis of ‘Ulwan’s work and supporting literature on educational axiology and the Rahmatan lil ‘Alamin paradigm, the study reveals that ‘Ulwan’s educational concept encompasses strengthening faith, cultivating morality, physical well-being, intellectual development, psychological stability, social competence, and sexual education, all of which axiology positions as essential to forming morally grounded individuals who contribute to civilization. Integration with the Rahmatan lil ‘Alamin perspective highlights the importance of a curriculum that is inclusive, humanistic, and transformative, emphasizing compassion, justice, and respect for human dignity. The study concludes that synthesizing ‘Ulwan’s ideas with the Rahmatan lil ‘Alamin paradigm can produce a comprehensive and contextually relevant model for Islamic child education that is adaptive to global challenges.